Lobectomy Versus Sublobectomy in Stage IIIA/N2 Non-Small Cell Lung Cancer: A Population-Based Study - Wang, Suyu; Zhang, Zhiyuan; Gu, Yang; Lv, Xin; Shi, Xuan; Liu, Meiyun (Frontiers in Oncology, 2021)
Background: The role lobectomy plays in stage IIIA/N2 non-small cell lung cancer (NSCLC) is controversial for a long time. What’s more, no previous study concentrates on whether sublobectomy can improve survival outcome for these patients, so we performed this population-based study to investigate whether stage IIIA/N2 NSCLC can benefit from these two surgery types and compare survival outcomes after lobectomy and sublobectomy. Methods: A total of 21,638 patients diagnosed with stage IIIA/N2 NSCLC between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database matched our selection criteria. The study cohort included patients received no surgery (n = 15,951), sublobectomy (n = 628) and lobectomy (n = 5,059). Kaplan-Meier method, Cox regression analyses and inverse probability of treatment weighting (IPTW)-adjusted Cox regression were used to illustrate the influence of sublobectomy and lobectomy on overall survival (OS) rates in the study cohort and compare these two surgery types. Results: Multivariable Cox regression analysis showed sublobectomy (HR: 0.584 [95%CI: 0.531-0.644], P value < 0.001; IPTW-adjusted HR:0.619 [95%CI:0.605-0.633], P value < 0.001) and lobectomy (HR: 0.439 [95%CI: 0.420-0.459], P value < 0.001; IPTW-adjusted HR:0.441 [95%CI:0.431-0.451], P value < 0.001) were both related to better OS rates compared with no surgery, and lobectomy exhibited better survival than sublobectomy (HR: 0.751 [95%CI: 0.680-0.0.830], P value < 0.001; IPTW-adjusted HR:0.713 [95%CI:0.696-0.731], P value < 0.001). Moreover, the results in subgroup analyses based on age, tumor size and radiotherapy and chemotherapy strategy in all study cohort were consistent. Conclusion: Stage IIIA/N2 NSCLC patients could benefit from sublobectomy or lobectomy, and lobectomy provided better OS rates than sublobectomy.